Research studies on educating for diversity and social justice - Esmail, Ashraf; Pitre, Abul; Lund, Darren E.; Baptiste, H. Prentice; Duhon-Owens, Gwendolyn (National Association for Multicultural Education (NAME), 2018)
"The book captures the various ways issues of diversity, equity and social justice unfold in educational settings and offers ideas for eradicating inequalities in schools. Concepts such as parental involvement, equity pedagogy, and dual language, among others, provide a template for assisting educators to improve educational outcomes for students"--